Calorimetric Study of Inulin as Cryo- and Lyoprotector of Bovine Plasma Proteins - Furlán, Laura T. Rodriguez; Lecot, Javier; Padilla, Antonio Pérez; Campderrós, Mercedes E.; Zaritzky, Noemi E. (IntechOpen, 2013)
None